Developing a Five-Tier Diagnostic Test to Identify Students’ Misconceptions in Science: An Example of the Heat Transfer Concepts - Rif’at Shafwatul Anam; Ari Widodo; Wahyu Sopandi; Hsin-Kai Wu (Elementary Education Online, 2023)
The purpose of this article is to propose a new diagnostic test that can be used to diagnose students’ deeper understanding of a concept and what they think about the concept. The instrument is a further development of the existing four-tier test by adding one more tier, drawing sub-microscopic representations. So, this new instrument is called a five-tier test. This instrument can diagnose students’ conceptions in more details and a window to student thinking that can help teachers in diagnosing students’ understanding. Concepts of heat transfer are chosen as the context for developing he instrument since they are considered as essential concepts in school science. The research involved 69 fifth-grade elementary school students from a school in Bandung-Indonesia. This study shows that the five-tier diagnostic test can be used to probe deeper understanding of students. It reveals that most elementary students know the concepts as at the macroscopic level but they had a lack of knowledge at the submicroscopic level. This study offer new instrument for diagnosing students’ understanding that can be useful for practical purpose as well as researchers.